The Effect of Distress on Susceptibility to False Memories - Monds, Lauren (2013)
False memories are of concern in situations involving eyewitness testimony, as inaccurate recollections of events may lead to false convictions. It is especially important to investigate the role of distress in the formation of false memories, due to many eyewitness testimony circumstances involving an event of a negative and traumatic nature. It was the aim of this thesis to investigate several key factors that may contribute to false memories for distressing events, namely Post-Traumatic Stress Disorder (PTSD) symptoms such as avoidance, intrusions, and dissociation, and also the biological marker of cortisol response. In order to investigate these aims, two main techniques were chosen: the Deese-Roediger-McDermott (DRM) word list procedure and the Trauma Film Paradigm (TFP) using narratives to introduce misinformation following the viewing of a film. In Experiment One participants completed the DRM using neutral and trauma-related words along with measu res of dissociation and biases related to threat. Analyses indicated that dissociation was related to false recall for traumatic stimuli; findings related to the biases were less straightforward. In Experiment Two misinformation was introduced following viewing of a neutral or stressful film. Findings indicated dissociation was related to higher distress ratings following the film, but unrelated to acceptance of misinformation. Avoidance scores were related to increased reporting and recognition of misinformation items and reported experiences of intrusions related to greater accuracy. Experiment Three was designed to address discrepant findings between that of the previous two experiments: namely that dissociation was significantly related to falsely remembering trauma words in the DRM task but did not predict false memories for the films. Participants completed both the DRM task and the film task. Results suggested that neither dissociation nor trauma history w as significantly related to DRM false recall. While the dist! ress and state dissociation results of Experiment Two were replicated (specifically that all were higher in response to the trauma film in comparison to the neutral film), the memory results were not. Accuracy on the DRM task predicted accuracy for the film task; however susceptibility to the DRM illusion was unrelated to susceptibility to the misinformation effect. This unexpected finding raised questions regarding whether all false memory tasks are equivalent. Experiment Four builds on the previous experiments by including a biological, objective measure of distress in response to film viewing: cortisol release. Cortisol responders were found to be more susceptible to the misinformation effect than non-responders, depending on sample timing. Dissociation was found to be related to cortisol response, and also confabulations for the film. Chapter Eight ties all four experiments together in the General Discussion. While several limitations were identified, it w as concluded that the findings of how distress experiences following the film affected memory were particularly novel. These findings have important practical implications regarding eyewitness testimony, as well as identifying people at risk of maladaptive distress reactions